Uni the unicorn. Uni's first sleepover - Ransom, Candice F., 1952-; Marlin, Lissy; Rosenthal, Amy Krouse; Barrager, Brigette (New York : Random House, 2019)
When Uni the unicorn goes to her first sleepover, the other girls are better at every game, but later Uni has the opportunity to share her special talent.
2.4
K-3
440L
J
Keywords: Unicorns -- Juvenile fiction; Sleepovers -- Juvenile fiction; Ability -- Juvenile fiction; Unicorns -- Fiction; Sleepovers -- Fiction; Ability -- Fiction; Fantasy; Fantasy fiction; Readers (Elementary)